Exploring language and linguistics - Braber, Natalie; Cummings, Louise; Morrish, Liz (cambridge university press, 2015)
"Introducting Language and Linguistics considers the key concepts of linguistics and the application of these concepts to real-world settings. The first eight chapters cover the standard topics of introduction to linguistics courses, while subsequent chapters introduce students to applied topics such as media discourse, literary linguistics and psycholinguistics. Each chapter has been written by a subject expert and experienced teacher, ensuring that the text is both up-to-date and clearly presented. Numerous learning features provide extensive student support: exercises allow students to review their understanding of key topics; summaries encourage students to reflect on the main points of each chapter; figures, photos, tables and charts clarify complex topics; and annotated suggestions for further reading point students to resources for self-study. A companion website, with 170 self-test questions, suggested group exercises, audio files and links to additional web resources, completes the learning package"--